Student Entrepreneurial Interest Entrepreneurial Knowledge and Social Media Usage - Rudi Yanto Batara Silalahi; Sahara Sahara (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this study is to determine and analyze the effect of entrepreneurial knowledge and the use of social media on student entrepreneurial interest, both individually and simultaneously. This research method is quantitative, uses multiple linear regression models, and applies statistical analysis using SPSS software version 26. The research population includes STIE Galileo students in the even semester of 2022/2023, and the sampling technique was carried out using the Slovin formula, which resulted in 74 students as randomly selected samples. The results of this study indicate a significant influence between entrepreneurial knowledge and the use of social media on student entrepreneurial interest, both partially and jointly. The findings of this study can strengthen entrepreneurial knowledge and social media utilization as an effort to stimulate students' entrepreneurial interest.